Effect of treatment of Helicobacter pylori with combination antibiotic therapy on iron deficiency anemia in patient with H. pylori-associated gastritis - Prashant Tanaji Dond; Rahul Deshpande; Shailesh Patil; Naresh Bhat (Asian Journal of Medical Sciences, 2023)
Background: The failure to identify a cause of iron deficiency in a substantial subset of patients with low iron stores raises the question of whether there are additional as of yet unexplained causes of iron depletion. Recently, there has been a growing body of evidence to suggest a relationship between Helicobacter pylori gastritis and iron deficiency anemia (IDA) in the absence of peptic ulcer disease. Aims and Objectives: Therefore, the present study was undertaken to investigate the effect of treatment of H. pylori with combination antibiotic therapy on IDA in patient with H. pylori-associated gastritis. Materials and Methods: The present study was carried out at a tertiary care hospital catering to a large population in south Solapur and nearby areas. The study was conducted for 2 years. All patients with IDA attending outpatient department and admitted to the hospital for 2 years, were included in the present study. All patients who have IDA according to the World Health Organization criteria, as a hemoglobin concentration <13 g/dL for men and <12 g/dL for women, a mean corpuscular volume (MCV) <75 fL and a serum ferritin level < 30 ng/mL, both in-patient and outpatient setting were evaluated with detail history, clinical examination, and investigation. Results: Baseline hemoglobin (Hb) in group I is 8.99±1.23, while in group II 7.55±2.08.All the parameters are comparable in groups I and II except baseline Hb%. There is a significant increase in Hb, packed cell volume (PCV), MCV, mean corpuscular hemoglobin (MCH), and MCH concentration (MCHC) after 2 months of treatment with oral iron therapy. There is a significant increase in Hb, PCV, MCV, MCH, and MCHC after 2 months of treatment with oral iron and triple therapy for H. pylori. Conclusion: Treatment of H. pylori infection was associated with more rapid and significant response to oral iron therapy in IDA as compared with the use of iron therapy alone.